Improvement of modeling on the Pidgeon process for magnesium production by introducing the variable thermophysical properties - Li, Rongbin; Wang, Chao; Wang, Zheng; Yang, Peixu; Xue, Fei; Liu, Fengqin; Zhang, Shaojun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
The variable thermophysical properties was introduced in the coupling model of heat transfer and reduction reaction in the Pidgeon process to improve the accuracy of numerical calculation in this paper. The distribution of temperature and magnesium reduction extent in the briquette layer, and overall magnesium reduction extent in the retort was investigated by the improved model. By introducing the variable thermophysical properties into the model, the overall magnesium reduction extent calculated were closer to the reality than those of the previous study, showing a better agreement with the statistical results of industrial production. The model results clearly presented the characteristic ‘Layer Shift’ in the briquette layer. The formed slag layer with lower thermal conductivity between the heat source and reaction interface makes it hard for the reaction to move forward inside layers, resulting into the slow magnesium production rate in the Pidgeon process. Consequently, the variable thermal conductivity in the range of 0.4 W×m-1×K-1~1.4 W×m-1×K-1 related to the briquette temperature and composition should be seriously considered in the high-accurate model. The improved model can provide a more accurate quantitative prediction in magnesium reduction in the Pidgeon process, which is of significance in innovation of key equipment and development of new magnesium production techniques.
Keywords: Magnesium; Pidgeon process; Numerical calculation; Heat transfer; Thermophysical property